2004
DOI: 10.1111/j.1471-0528.2004.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Do maternity care provider groups have different attitudes towards birth?

Abstract: Objective To compare family physicians', obstetricians' and midwives' self-reported practices, attitudes and beliefs about central issues in childbirth. Design Mail-out questionnaire.Setting/Population All registered midwives in the province, and a sample of family physicians and obstetricians in a maternity care teaching hospital. Response rates: 91% (n ¼ 50), 69% (n ¼ 97) and 89% (n ¼ 34), respectively. Methods A postal survey.Main outcome measures Twenty-three five-point Likert scale items (strongly agree t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 23 publications
2
78
0
Order By: Relevance
“…In contrast, many studies have addressed collaboration between nursing staff and physicians. 4,5 Primary care medicine has long recognized the need for interprofessional practice, with many models of highperformance teams. Several characteristics have been identified in high-performance teams, including effective communication, recognition of member contributions, shared decision-making, and shared vision and values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, many studies have addressed collaboration between nursing staff and physicians. 4,5 Primary care medicine has long recognized the need for interprofessional practice, with many models of highperformance teams. Several characteristics have been identified in high-performance teams, including effective communication, recognition of member contributions, shared decision-making, and shared vision and values.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly different responses on knowledgebased questions showed that family practitioners and midwives were more skeptical about the external validity of the literature on issues such as induction of labour. 5 An independent inquiry into the safety of maternity services in England in 2008, ''Safe Births: Everybody's business'', concluded that ''safe teams'' are the key to improving the safety of maternity care. The inquiry found a number of recurrent difficulties in teamwork performance such as those related to interprofessional relationships, leadership and management, and communication.…”
mentioning
confidence: 99%
“…Among the general public there is an agreement that women have the right to choose both on the basis of concern with bodily integrity and because of fear of childbirth (4). However, among professionals there are contradictory opinions (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy the pregnant woman should be given adequate and balanced information on issues concerning mode of delivery and other health matters related to the delivery. Some studies have shown that there are differences in maternal caregivers opinions' on how they think one should deal with the woman's wishes and also on what might be an acceptable rate of cesarean section (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Legal liability, for example, creates an awareness that has an impact on midwives as well as obstetricians and gynaecologist's decision-making and attitudes towards mode of delivery (Reime B et al 2004). Most studies have focused on obstetricians and gynaecologists' attitudes towards elective CS but little is known about midwives attitudes and opinions about CS.…”
Section: Introductionmentioning
confidence: 99%